Public-Private Partnership as a Tool for Financing Infrastructure Projects in Algeria (مجلة الواحات للبحوث والدراسات, 2022)
Infrastructure is one of the most important elements of development that requires huge capitals. Financing infrastructure in Algeria depends entirely on the public treasury, which will not be possible in the future because of the decline in oil revenues. This paper tries to highlight the current state of infrastructure in Algeria, and the challenges that should be faced to provide the convenient environment for adopting public private partnership to finance infrastructure projects.keywords: infrastructure; public private partnership, public expenditure, public treasury, public investments.